ENVIRONMENTAL EDUCATION AS A MEANS OF SUSTAINABLE AND RESPONSIBLE TOURISM DEVELOPMENT - Solahuddin Nasution; Walid Musthafa Sembiring; Femmy I. Dalimunthe; Edi Sumarno; Mujahid Widian Saragih; Moulita (SOSIOEDUKASI, 2025)
The development of global and national tourism faces serious challenges related to environmental degradation due to unsustainable mass tourism practices. This study aims to analyze the strategic contribution of environmental education to the development of sustainable and responsible tourism in Indonesia. The research uses a qualitative approach with a systematic literature review method, based on the perspective of environmental sociology and critical education. The data sources consist of scientific journal articles, academic books, policy reports, as well as relevant case studies, collected through databases such as Scopus, Google Scholar, and DOAJ. The data collection technique is carried out through thematic tracing, while the data analysis is carried out interpretively with a thematic approach. The results of the study show that environmental education is able to increase ecological awareness, form ethical tourism behavior, and strengthen the conservation of local natural resources and culture. Implementation challenges include limited resources, resistance from industry players, and lack of policy support. However, community-based and participatory educational approaches have proven effective in a number of tourist destinations. The conclusions of this study affirm the importance of integrating environmental education in tourism management policies, curricula, and practices to support more equitable, inclusive, and sustainable development.